Freud's Britain: Family, followers and the dissemination of ideas before and after the Great War - Willoughby, RT (2022)

(untitled)
Existing histories of psychoanalysis have by and large paid scant attention to the role the Freud family played in Freud’s mental economy, this neglect being most conspicuous with respect to the British branch of the family. Various family members are glimpsed in Freud’s published correspondence and some – notably his nephew John – appear as key characters in the Interpretation of Dreams and other works. This latter observation points to the importance of Freud’s Britain: Freud’s reflections on his own life experiences, with his close-knit family, became indispensable building blocks in his theorising, both for Freud and subsequent psychoanalytic generations. Through a fine-grained study of Emanuel and Philipp Freud (and their families), the variegated influence of these British Freuds on their younger brother is here revealed for the first time. These relationships shaped Freud’s thinking, attitudes, and theorising. They strengthened, if not created, his Anglophilia. Freud’s Britain thus allows for a better contextualised understanding of the actual sibling and familial ties that went into forming the tapestry of psychoanalysis.